10‐year prospective cohort follow‐up of immediately restored XiVE implants. Issue 6 (21st June 2015) - Degidi, Marco; Nardi, Diego; Piattelli, Adriano
Abstract: Objective: The aim of this prospective cohort study was to assess the ten‐year performance of the condensing thread, self‐tapping apex and internal hexagonal connection XiVE implant supporting partial fixed prostheses placed with an immediate restoration approach. Material and methods: All patients received a fixed two‐ to four‐unit partial provisional restoration supported by immediately loaded implants. The final gold alloy/ceramic restorations were cemented approximately 28 weeks after implant insertion. Marginal bone level, pocket probing depth and percentage of bleeding on probing, biological or technical complications and any other adverse events were measured annually up to ten years after surgery. The overall success and survival rates at implant level were evaluated following the International Congress of Oral Implantologists (ICOI) Pisa Consensus Conference criteria. Implant placement in post‐extractive or healed sites, smoking and a history of periodontal treatment were evaluated to assess whether they had an influence on bone resorption or on implant survival. Results: Of 114 patients, for a total of 284 implants, fulfilled all the inclusion criteria and were enrolled in the study. 78 (27.5%) implants placed in 30 (26.3%) patients were lost to follow‐up. Eight of 284 (2.8%) implants failed in 8 of 114 (7.0%) patients: one (12.5% of losses) due to failure to achieve osseointegration and seven (87.5% of losses) due to peri‐implantitis. No cluster implant failures were assessed. The failure of the implant caused the failure of the prosthesis due to the strategic position of the implant in four patients. At the final ten‐year follow‐up, 121 (61.4%) implants exhibited a "full success" status with an optimal health condition, 21 (10.9%) implants scored a "satisfactory survival" condition, while 49 (25.49%) of the implants were classified as "compromised survival" status (Misch et al. 2008). Smoking was found to be statistically associated with "implant failure" ( P  = 0.010), while no association was found for patients treated for periodontal disease ( P  = 0.679) and post‐extractive surgical sites ( P  = 0.664). Statistically significant more marginal bone loss was found in patients treated for periodontal disease ( P  < 0.0001). An increased bone loss was also observed in smokers, but the difference with the non‐smokers was not statistically significant ( P  = 0.06). Conclusions: The XiVE implants can be successfully used to support immediate prosthesis. Patients with a history of periodontitis show increased bone loss and risk to develop peri‐implant disease. Smoking seems to jeopardize the long‐term implant survival.